Endocrine-disrupting effects of methylparaben on the adult gerbil prostate - Costa, Janaína R.; Campos, Mônica S. [UNESP]; Lima, Rodrigo F.; Gomes, Liana S.; Marques, Mara R.; Taboga, Sebastião R. [UNESP]; Biancardi, Manoel F.; Brito, Pedro V. A.; Santos, Fernanda C. A. (Wiley, 2017)
Parabens are xenoestrogens widely employed in cosmetics, foodstuffs, and pharmaceutical products. These chemicals are known to disrupt hormone-dependent organs, due to their binding affinity for hormonal receptors. Although recent studies have evaluated the endocrine-disrupting potential of parabens in several reproductive organs, few have investigated the effects of these chemicals in the prostate. The aim of this work was to evaluate the effects of oral exposure to methylparaben (500 mg/kg/day) for 3, 7, and 21 days on male and female adult gerbil prostate. For this purpose, we employed biometrical, morphological, and immunohistochemical analyses. The results showed that methylparaben caused morphological changes in gerbil prostates in all experimental groups. These animals displayed similar alterations such as prostate epithelial hyperplasia, increased cell proliferation, and a higher frequency of AR-positive cells. However, the prostate of the female gerbil showed additional changes such as stromal inflammatory infiltration, intraepithelial neoplasia foci, and an increase in AR-positive frequency. Altogether, these data show that methylparaben was responsible for disrupting estrogenic and androgenic receptors, suggesting that parabens may have estrogenic and antiandrogenic effects in the prostate.
Keywords: androgen receptor; antiandrogens; estrogen agonist; female prostate; parabens